2019
DOI: 10.1021/acs.est.9b02073
|View full text |Cite
|
Sign up to set email alerts
|

Selective Ingestion and Egestion of Plastic Particles by the Blue Mussel (Mytilus edulis) and Eastern Oyster (Crassostrea virginica): Implications for Using Bivalves as Bioindicators of Microplastic Pollution

Abstract: Microplastics (MP; 1 μm to 1 mm) of various shapes and compositions are ingested by numerous marine animals. Recently, proposals have been made to adopt bivalve molluscs as bioindicators of MP pollution. To serve as indicators of MP pollution, however, the proposed organisms should ingest, without bias, the majority of plastic particles to which they are exposed. To test this premise, eastern oysters, Crassostrea virginica, and blue mussels, Mytilus edulis, were offered variously sized polystyrene microspheres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(126 citation statements)
references
References 67 publications
7
115
1
3
Order By: Relevance
“…In mussels, waterborne particles are captured via the gills, with capture efficiency and ingestion dependent upon particle size, shape, hydrophobicity, and aggregation within biogenic matrices (e.g. marine snow) (Kach and Ward, 2008;Porter et al, 2018;Rosa et al, 2018;Ward and Targett, 1989;Ward and Shumway, 2004); particles are subsequently sorted via the labial palps (Beninger et al, 1995), and either ingested or ejected within pseudofaeces (Ward et al, 2019b;Zhao et al, 2018). Microplastics have been shown to aggregate in the gills and digestive glands (Avio et al, 2015;Browne et al, 2008;Paul-Pont et al, 2016;Pittura et al, 2018;Revel et al, 2019;von Moos et al, 2012) and adhere on organs not associated with feeding, including the adductor muscles, foot and mantle (Kolandhasamy et al, 2018); there is also some evidence that <20 µm microplastics can translocate into the haemolymph (Browne et al, 2008;von Moos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In mussels, waterborne particles are captured via the gills, with capture efficiency and ingestion dependent upon particle size, shape, hydrophobicity, and aggregation within biogenic matrices (e.g. marine snow) (Kach and Ward, 2008;Porter et al, 2018;Rosa et al, 2018;Ward and Targett, 1989;Ward and Shumway, 2004); particles are subsequently sorted via the labial palps (Beninger et al, 1995), and either ingested or ejected within pseudofaeces (Ward et al, 2019b;Zhao et al, 2018). Microplastics have been shown to aggregate in the gills and digestive glands (Avio et al, 2015;Browne et al, 2008;Paul-Pont et al, 2016;Pittura et al, 2018;Revel et al, 2019;von Moos et al, 2012) and adhere on organs not associated with feeding, including the adductor muscles, foot and mantle (Kolandhasamy et al, 2018); there is also some evidence that <20 µm microplastics can translocate into the haemolymph (Browne et al, 2008;von Moos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These authors concluded that their study emphasised the gap of knowledge on the feeding behaviour of mussels in relation to MPs, in this case, fragments and the necessity to investigate it in different marine species and under different exposure regimes. Ward et al [20] unequivocally showed that the selective ingestion and egestion of plastic particles by the blue mussel and Eastern oyster (C. virginica) precludes their use as bioindicators of MPs pollution. These authors advised, given recent proposals to adopt bivalve molluscs that filter feed from the water column as bioindicators of MPs pollution (e.g., [15]), the proposed organisms should ingest without bias the majority of plastic particles to which they are exposed.…”
Section: Laboratory Researchmentioning
confidence: 99%
“…As noted within the introduction, the well mixed nature of the water column due to currents, wind and storm events would preclude assigning a particular source of plastic microfiber contamination to the shellfish. More importantly though are the conclusions and subsequent advice of Ward et al [20] who state that filter feeders such as the oyster, because of their bias in food ingestion cannot be used as biomonitors of MPs thus rendering the observations and conclusions of Covernton et al [40] with respect to the oyster unsubstantiated.…”
Section: Plos Onementioning
confidence: 99%
“…Blue mussels and eastern oysters were used in a laboratory experiment to compare ingestion and egestion of spherical and fibrous microplastics (Ward et al, 2019). Both species rejected larger spheres (1,000 μm) at a higher rate than smaller spheres and rejected a higher proportion of large microspheres than long microfibers.…”
Section: Effects Of Microplastic Debrismentioning
confidence: 99%